Zur generierung von wissen in interpretationsgruppen. Methodologische reflexionen im kontext reflexiver elitebildungsforschung - Schippling, A.; Alvares, M. (Zeitschrift für Qualitative Forschung, 2019)
Although it has become common practice in scientific daily life, the interpretation work in groups and workshops and the generation of knowledge in these groups are still rarely studied. Taking into consideration the dimension of reflexivity in the process of knowledge generation in group interpretation in the context of research on elite formation, we developed methodological reflexions based on empirical insights in the interpretation practice of a research workshop in a Portuguese university. Subsequently, research potentials and perspectives related to the social practice and knowledge generation in interpretation groups will be presented, which also include a transcultural perspective.